Makna Hidup Berkelompok pada Masyarakat Jepang - Sartini, Sartini; Muhni, Djuretna Adi Imam (Jurnal Filsafat "WISDOM", 2000)
The relationship of individual man and society is natural. The individual man will never exist outside his society. The individual can be more dominant than the society or vice versa. In Japan, society or group posseses a stronger role than individual. Japan is well known with its groupism. This sense leads Japan to mastering sciences, technology, and economics fields. The objectives of this research are: a) to know the phenomena of collective life; b) to kwon the dialougue between the conservative collective life and the penetration of the modern values; c) to know Japanese cultural values that bases itself on groupism and leads Japan to be a modern society.This research is a bibbliographical study, using hermeneutics with its three steps: description, interpretation, and philosophical reflection. This research is started with collecting data than describing the groupism phenomena in Japan. The compiled data are analysed and interpreted to find the meaning or values of the groupism of collective life phenomena. Philosophical reflection is used to analysed human and social cost of development. Finally, the result of the research are reported after revision.The result of this study that, first Japanese society is an organizational society. Second, Japanese development and success has changed the society to a complex culture with its pragmatic materialistic, individualistic, and hedonistic attitude. However, the Japanese traditional values have become the root of the development of the Japanese modern corporation that manifested itself on the ethical code of the companies. Third, Japanese groupism with is sense of organization is very accomodative to modern bussiness ethics.